"PSYCHOLOGICAL EFFECTS OF COLORS AND COLOR THERAPY": ‘‘रंगों का मनोवैज्ञानिक प्रभाव एवं रंग चिकित्सा’’ - Atre, Veena (International Journal of Research -GRANTHAALAYAH, 2014)
Man is a social animal. Different colors have a significant impact on his life. All colors make sense of meaning in life. Provide energy with positive thinking. Only then does man lead a life of plight and activity, through painting, various colors have an important role in the physical and mental development of man. Artists express not only expressions of mind with lines and colors, but behind them research and conceptual brainstorming also develop with development. मनुष्य एक सामाजिक प्राणी है। विभिन्न रंगों का उसके जीवन पर महत्वपूर्ण प्रभाव पड़ता है। सभी रंग जीवन में सार्थकता का अनुभव कराते है। सकारात्मक सोच के साथ ऊर्जा प्रदान करते हैं। तभी मनुष्य सरसता एवं सक्रियता के साथ जीवन व्यतीत करता है चित्रकला के माध्यम से मनुष्य के शारीरिक एवं मानसिक विकास में विभिन्न रंगों की अहम् भूमिका है। कलाकार केवल मन के भाव ही रेखा और रंगों से अभिव्यक्त नहीं करते बल्कि उसके पीछे उनका शोध एवं वैचारिक मंथन के साथ क्रिएशन काम्बीनेशन का भी विकास होता है।